Translation: The Interfaces of Language and Technology - Bréard, Andrea; Tamborini, Marco (Technology and Language, 2024)
The many languages in which technological objects are written – visual, natural, symbolic, olfactory, artefactual, etc. – and the many ways in which technology is used to translate between these languages raises a series of philosophical questions. This editorial surveys some of these questions, providing a brief introduction to the growing interest in the concept and practices of translation as a key to understanding our relationship with and the production of technological objects and knowledge forms. We focus on epistemological aspects of the linguistic and grammatical turn in technology studies and anthropological questions of the use of translation as an epistemological tool to better delineate the characteristics of the human being. Finally, the seven articles contained in this special issue on Translation - Theory and Technology are briefly presented in terms of their common thematic and philosophical approache
Keywords: Epistemology of translation; Anthropology of translation; Transcultural conceptual change; Homo translator